The Role of Financial Intelligence Strategies in Achieving the Dimensions of Financial Success - األشخاذ اىٍصاغد اىدنخٔر ضهٍج رش٘د; األشخاذ اىٍصاغد اىدنخٔر دىشاد ضت٘ب (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Touched on the subject of financial intelligence strategies of the foundations of the calibration and measurement results and financial art of finance and investment and the mechanics of analyzing the figures and cash flow and profit and finally knowledge of financial transparency systems, also touched on the subject of the dimensions of the financial success of competitive advantage and customer satisfaction, and providing banking services and to achieve returns. The study aims to examine the role of financial intelligence strategies to achieve the dimensions of financial success, it has been selected commercial banks in Duhok province to conduct field side of the search, which included research (44) of the leaders of these banks managers and assistants directors and heads of departments, and adopted the researchers questionnaire form after It has been confirmed validity and reliability as a tool head for the collection of field data side, data were analyzed using standard deviations and simple linear regression analysis of the Pearson correlation 220 coefficient